Lawsonia intracellularis in pigs: progression of lesions and Involvement of apoptosis - Guedes, Roberto M. C. (2017)
The purpose of this study was to follow the progression of gross and histologic lesions and apoptosis events in Lawsonia intracellularis- infected enterocytes through the course of the disease, proliferative enteropathy (PE). Thirty 5-week-old pigs were divided into 2 groups: 20 challenged and 10 control animals. Groups of 3 pigs, 2 challenged and 1 control, were euthanized at 1, 3, 5, 8, 11, 15, 19, 24, 29, and 35 days after inoculation. Complete necropsies were performed with gross evaluation. Tissue samples from different sites of the gastrointestinal tract and other visceral organs were collected for routine histologic staining and for immunohistochemistry (IHC) for L. intracellularis. In addition, caspase-3, terminal deoxyuridine nick-end labeling assay, and electron microscopy were performed in ileum samples. Macroscopic and histologic lesions suggestive of PE were first detected 11 days after infection and continued through day 24. L. intracellularis antigen was first detected in the intestine by IHC on day 5 after inoculation, and the bacterium was first detected by transmission electron microscopy on day 15. Positive IHC staining for [L. intracellularis] and enterocyte proliferation, but no gross lesion, were detected on day 29. All 3 pigs euthanized on day 35 were grossly and histologically normal and IHC negative. Hyperplastic crypts in challenge pigs had more apoptotic cells on days 15, 19, and 24 postinfection (P < .05) compared to control pigs. Our results demonstrated the progression of lesions and infection by L. intracellularis and that inhibition of enterocyte apoptosis is not involved in the pathogenesis of proliferative enteropathy.